Physical and chemical investigation of water and sediment of the Keban Dam Lake, Turkey - Part 1: Iso-curves of radioactivity - Kulahci, F.; Dogru, M. (Springer, 2006)
The gross alpha- gross beta-activity, Cs-137 and Sr-90 in the water and sediment samples taken from the Keban Dam Lake. Uluova Region. was investigated in 2003 and 2004. We have found that in spring the concentration of (CS)-C-137 in the surface water and deep sediment changed between 0.001-0.01 Bq/l (0.4-2.5 Bq(.)kg(-1)) that of Sr-90 between 0.0001-0.009 Bq/l (0.1-9 Bq(.)kg(-1)) and in autumn the values were 0.0001-0.009 Bq/l (0.4-8 Bq(.)kg(-1)) for Cs-137 and 0.0002-0.005 Bq/l (0.6-4 Bq(.)kg(-1)) for 90Sr. respectively. The results were presented in form of iso-curves.
Keywords: Chernobyl Accident; Hazar Lake; Uranium; Elazig; Soil